Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure! Let's solve each of the parts step by step for the given geometric sequences.
### Part a:
Given:
- First term, [tex]\( a_1 = 16 \)[/tex]
- Common ratio, [tex]\( r = \frac{1}{2} \)[/tex]
- Number of terms, [tex]\( n = 7 \)[/tex]
We need to find the sum [tex]\( S_n \)[/tex] of the first 7 terms of this geometric series.
The formula to calculate the sum [tex]\( S_n \)[/tex] of the first [tex]\( n \)[/tex] terms of a geometric sequence is:
[tex]\[ S_n = a_1 \frac{1 - r^n}{1 - r} \][/tex]
Substitute the given values:
[tex]\[ S_7 = 16 \cdot \frac{1 - \left(\frac{1}{2}\right)^7}{1 - \left(\frac{1}{2}\right)} \][/tex]
Therefore, the sum [tex]\( S_7 \)[/tex] is:
[tex]\[ S_7 = 31.75 \][/tex]
### Part b:
Given:
- First term, [tex]\( a_1 = 4 \)[/tex]
- Last term, [tex]\( a_n = 256 \)[/tex]
- Common ratio, [tex]\( r = 4 \)[/tex]
We need to find the sum [tex]\( S_n \)[/tex] of the terms up to [tex]\( a_n = 256 \)[/tex], but first we need to determine the number of terms [tex]\( n \)[/tex].
The general term [tex]\( a_n \)[/tex] of a geometric sequence is given by:
[tex]\[ a_n = a_1 \cdot r^{n-1} \][/tex]
[tex]\[ 256 = 4 \cdot 4^{n-1} \][/tex]
Divide both sides by 4:
[tex]\[ 64 = 4^{n-1} \][/tex]
Since [tex]\( 64 = 4^3 \)[/tex], we get:
[tex]\[ 4^3 = 4^{n-1} \][/tex]
Thus:
[tex]\[ n - 1 = 3 \][/tex]
[tex]\[ n = 4 \][/tex]
Now we can find [tex]\( S_n \)[/tex]:
[tex]\[ S_n = a_1 \cdot \frac{1 - r^n}{1 - r} \][/tex]
Substitute the values:
[tex]\[ S_4 = 4 \cdot \frac{1 - 4^4}{1 - 4} \][/tex]
Therefore, the sum [tex]\( S_4 \)[/tex] is:
[tex]\[ S_4 = 340.0 \][/tex]
### Part c:
Given:
- First term, [tex]\( a_1 = 1 \)[/tex]
- Fifth term, [tex]\( a_5 = \frac{1}{16} \)[/tex]
- Common ratio, [tex]\( r = -\frac{1}{2} \)[/tex]
We need to find the sum [tex]\( S_n \)[/tex] of the first 5 terms.
First, verify the common ratio:
[tex]\[ a_5 = a_1 \cdot r^{4} \][/tex]
[tex]\[ \frac{1}{16} = 1 \cdot \left(-\frac{1}{2}\right)^4 \][/tex]
[tex]\[ \frac{1}{16} = \frac{1}{16} \][/tex]
Thus, the common ratio [tex]\( r \)[/tex] is correct.
Now calculate [tex]\( S_n \)[/tex]:
[tex]\[ S_5 = a_1 \cdot \frac{1 - r^5}{1 - r} \][/tex]
Substitute the values:
[tex]\[ S_5 = 1 \cdot \frac{1 - \left(-\frac{1}{2}\right)^5}{1 - \left(-\frac{1}{2}\right)} \][/tex]
Therefore, the sum [tex]\( S_5 \)[/tex] is:
[tex]\[ S_5 = 0.6875 \][/tex]
### Part d:
Given:
- Sum of the first 4 terms, [tex]\( S_4 = 30 \)[/tex]
- Common ratio, [tex]\( r = -2 \)[/tex]
- Number of terms, [tex]\( n = 4 \)[/tex]
We need to find the first term [tex]\( a_1 \)[/tex] and the first three terms of the sequence.
The formula for [tex]\( S_n \)[/tex] is:
[tex]\[ S_n = a_1 \cdot \frac{1 - r^n}{1 - r} \][/tex]
Substitute the given values:
[tex]\[ 30 = a_1 \cdot \frac{1 - (-2)^4}{1 - (-2)} \][/tex]
[tex]\[ 30 = a_1 \cdot \frac{1 - 16}{1 + 2} \][/tex]
[tex]\[ 30 = a_1 \cdot \frac{-15}{3} \][/tex]
[tex]\[ 30 = a_1 \cdot (-5) \][/tex]
[tex]\[ a_1 = -6 \][/tex]
Now, find the first three terms of the sequence:
First term [tex]\( a_1 \)[/tex]:
[tex]\[ a_1 = -6 \][/tex]
Second term [tex]\( a_2 \)[/tex]:
[tex]\[ a_2 = a_1 \cdot r = -6 \cdot (-2) = 12 \][/tex]
Third term [tex]\( a_3 \)[/tex]:
[tex]\[ a_3 = a_2 \cdot r = 12 \cdot (-2) = -24 \][/tex]
Therefore, the first three terms of the sequence are:
[tex]\[ -6, 12, -24 \][/tex]
In summary:
- Part a: [tex]\( S_7 = 31.75 \)[/tex]
- Part b: [tex]\( S_4 = 340.0 \)[/tex]
- Part c: [tex]\( S_5 = 0.6875 \)[/tex]
- Part d: The first three terms are [tex]\( -6, 12, -24 \)[/tex]
### Part a:
Given:
- First term, [tex]\( a_1 = 16 \)[/tex]
- Common ratio, [tex]\( r = \frac{1}{2} \)[/tex]
- Number of terms, [tex]\( n = 7 \)[/tex]
We need to find the sum [tex]\( S_n \)[/tex] of the first 7 terms of this geometric series.
The formula to calculate the sum [tex]\( S_n \)[/tex] of the first [tex]\( n \)[/tex] terms of a geometric sequence is:
[tex]\[ S_n = a_1 \frac{1 - r^n}{1 - r} \][/tex]
Substitute the given values:
[tex]\[ S_7 = 16 \cdot \frac{1 - \left(\frac{1}{2}\right)^7}{1 - \left(\frac{1}{2}\right)} \][/tex]
Therefore, the sum [tex]\( S_7 \)[/tex] is:
[tex]\[ S_7 = 31.75 \][/tex]
### Part b:
Given:
- First term, [tex]\( a_1 = 4 \)[/tex]
- Last term, [tex]\( a_n = 256 \)[/tex]
- Common ratio, [tex]\( r = 4 \)[/tex]
We need to find the sum [tex]\( S_n \)[/tex] of the terms up to [tex]\( a_n = 256 \)[/tex], but first we need to determine the number of terms [tex]\( n \)[/tex].
The general term [tex]\( a_n \)[/tex] of a geometric sequence is given by:
[tex]\[ a_n = a_1 \cdot r^{n-1} \][/tex]
[tex]\[ 256 = 4 \cdot 4^{n-1} \][/tex]
Divide both sides by 4:
[tex]\[ 64 = 4^{n-1} \][/tex]
Since [tex]\( 64 = 4^3 \)[/tex], we get:
[tex]\[ 4^3 = 4^{n-1} \][/tex]
Thus:
[tex]\[ n - 1 = 3 \][/tex]
[tex]\[ n = 4 \][/tex]
Now we can find [tex]\( S_n \)[/tex]:
[tex]\[ S_n = a_1 \cdot \frac{1 - r^n}{1 - r} \][/tex]
Substitute the values:
[tex]\[ S_4 = 4 \cdot \frac{1 - 4^4}{1 - 4} \][/tex]
Therefore, the sum [tex]\( S_4 \)[/tex] is:
[tex]\[ S_4 = 340.0 \][/tex]
### Part c:
Given:
- First term, [tex]\( a_1 = 1 \)[/tex]
- Fifth term, [tex]\( a_5 = \frac{1}{16} \)[/tex]
- Common ratio, [tex]\( r = -\frac{1}{2} \)[/tex]
We need to find the sum [tex]\( S_n \)[/tex] of the first 5 terms.
First, verify the common ratio:
[tex]\[ a_5 = a_1 \cdot r^{4} \][/tex]
[tex]\[ \frac{1}{16} = 1 \cdot \left(-\frac{1}{2}\right)^4 \][/tex]
[tex]\[ \frac{1}{16} = \frac{1}{16} \][/tex]
Thus, the common ratio [tex]\( r \)[/tex] is correct.
Now calculate [tex]\( S_n \)[/tex]:
[tex]\[ S_5 = a_1 \cdot \frac{1 - r^5}{1 - r} \][/tex]
Substitute the values:
[tex]\[ S_5 = 1 \cdot \frac{1 - \left(-\frac{1}{2}\right)^5}{1 - \left(-\frac{1}{2}\right)} \][/tex]
Therefore, the sum [tex]\( S_5 \)[/tex] is:
[tex]\[ S_5 = 0.6875 \][/tex]
### Part d:
Given:
- Sum of the first 4 terms, [tex]\( S_4 = 30 \)[/tex]
- Common ratio, [tex]\( r = -2 \)[/tex]
- Number of terms, [tex]\( n = 4 \)[/tex]
We need to find the first term [tex]\( a_1 \)[/tex] and the first three terms of the sequence.
The formula for [tex]\( S_n \)[/tex] is:
[tex]\[ S_n = a_1 \cdot \frac{1 - r^n}{1 - r} \][/tex]
Substitute the given values:
[tex]\[ 30 = a_1 \cdot \frac{1 - (-2)^4}{1 - (-2)} \][/tex]
[tex]\[ 30 = a_1 \cdot \frac{1 - 16}{1 + 2} \][/tex]
[tex]\[ 30 = a_1 \cdot \frac{-15}{3} \][/tex]
[tex]\[ 30 = a_1 \cdot (-5) \][/tex]
[tex]\[ a_1 = -6 \][/tex]
Now, find the first three terms of the sequence:
First term [tex]\( a_1 \)[/tex]:
[tex]\[ a_1 = -6 \][/tex]
Second term [tex]\( a_2 \)[/tex]:
[tex]\[ a_2 = a_1 \cdot r = -6 \cdot (-2) = 12 \][/tex]
Third term [tex]\( a_3 \)[/tex]:
[tex]\[ a_3 = a_2 \cdot r = 12 \cdot (-2) = -24 \][/tex]
Therefore, the first three terms of the sequence are:
[tex]\[ -6, 12, -24 \][/tex]
In summary:
- Part a: [tex]\( S_7 = 31.75 \)[/tex]
- Part b: [tex]\( S_4 = 340.0 \)[/tex]
- Part c: [tex]\( S_5 = 0.6875 \)[/tex]
- Part d: The first three terms are [tex]\( -6, 12, -24 \)[/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.